Penerapan Aturan Anti Dumping Terhadap Penjualan Produk Impor Melalui E-Commerce - Muhammad Yoni (Indragiri Law Review, 2025)
Dumping practices, where imported products are sold at prices lower than the domestic market value, can harm domestic industries and disrupt the stability of a country's economy. In today's digital era, e- commerce has grown rapidly, allowing imported products to be sold directly to domestic consumers without intermediaries. This creates new challenges in applying anti-dumping regulations, as it is difficult to monitor cross-border transactions that occur online. This study aims to analyze the challenges and solutions in implementing anti- dumping rules for imported products sold through e-commerce platforms. The research uses a qualitative approach with a literature review and policy analysis. The findings indicate that monitoring e- commerce transactions requires more adaptive regulations and advanced technologies, such as big data and artificial intelligence, to detect dumping practices. Additionally, international cooperation and strengthening e-commerce platform regulations are key to addressing this issue. Policies that enhance price transparency and product origin on e-commerce platforms, as well as clear and accountable law enforcement, are essential to protect domestic industries. This study is expected to contribute to the development of international trade policies and anti-dumping regulations in the digital age